BIM in off-site manufacturing for buildings. (November 2017) - Abanda, F.H.; Tah, J.H.M.; Cheung, F.K.T.
Abstract: The need to overcome challenges faced by construction industry has been at the core of many government reports. Most of the reports suggest the adoption of innovations including off-site manufacture and emerging Building Information Modelling (BIM) to overcome the challenges facing the industry. Current research has largely focused on the impacts of off-site manufacture and BIM independently applied on traditional construction methods. Due to the factory-based nature of off-site manufacture, the benefits of BIM on off-site manufacture have been widely argued to be far greater than those of traditional construction. However, studies about impacts of BIM on off-site manufacture are scarce with far too many on traditional construction. This study investigates the implications of BIM systems on off-site manufacture and traditional construction methods, with emphasis on the technological potential of BIM for off-site manufacture. The specific objectives of the study are threefold. Firstly, it examines how BIM can support off-site manufacture. Secondly, the paper discusses the benefits of BIM and explains how BIM can overcome barriers hindering the uptake of off-site manufacturing. Thirdly, due to the importance to measure the benefits to support wider adoption, an examination of the published quantitative benefits of BIM on off-site manufacture and traditional construction is undertaken. A critical appraisal of the literature was undertaken to achieve the aim of this study. The main findings are the identification of qualitative and quantitative benefits of: BIM on off-site manufacture, off-site manufacture and BIM on traditional construction. The findings reinforce the argument that BIM adoption on off-site manufacturing projects is a rapid, efficient and one of the best ways to improve on the long standing challenges that have plagued the construction industry for generations. Highlights: Off-site manufacture (OSM) contributes to construction efficiency and productivity. BIM facilitates the deployment of OSM. BIM + OSM leads to greater efficiency and productivity in the construction industry.